Open-Label, Single-Arm, Phase II Study of Pembrolizumab Monotherapy as First-Line Therapy in Patients With Advanced Non–Clear Cell Renal Cell Carcinoma. Issue 9 (20th March 2021) - McDermott, David F.; Lee, Jae-Lyun; Ziobro, Marek; Suarez, Cristina; Langiewicz, Przemyslaw; Matveev, Vsevolod Borisovich; Wiechno, Pawel; Gafanov, Rustem Airatovich; Tomczak, Piotr; Pouliot, Frederic; Donskov, Frede; Alekseev, Boris Yakovlevich; et al.
Abstract : PURPOSE: Programmed death 1 (PD-1) pathway inhibitors have not been prospectively evaluated in patients with non–clear cell renal cell carcinoma (nccRCC). The phase II KEYNOTE-427 study (cohort B) was conducted to assess the efficacy and safety of single-agent pembrolizumab, a PD-1 inhibitor, in advanced nccRCC. METHODS: Patients with histologically confirmed, measurable (Response Evaluation Criteria in Solid Tumors [RECIST] version 1.1) nccRCC and no prior systemic therapy received pembrolizumab 200 mg intravenously once every 3 weeks for ≤ 24 months. The primary end point was objective response rate (ORR) per RECIST v1.1. RESULTS: Among enrolled patients (N = 165), 71.5% had confirmed papillary, 12.7% had chromophobe, and 15.8% had unclassified RCC histology. Most patients (67.9%) had intermediate or poor International Metastatic RCC Database Consortium risk status and tumors with programmed death ligand 1 (PD-L1) combined positive score (CPS) ≥ 1 (61.8%). The median time from enrollment to database cutoff was 31.5 months (range, 22.7-38.8). In all patients, the ORR was 26.7%. The median duration of response was 29.0 months; 59.7% of responses lasted ≥ 12 months. The ORR by CPS ≥ 1 and CPS < 1 status was 35.3% and 12.1%, respectively. The ORR by histology was 28.8% for papillary, 9.5% for chromophobe, and 30.8% for unclassified. Overall, the median progression-free survival was 4.2 months (95% CI, 2.9 to 5.6); the 24-month rate was 18.6%. The median overall survival was 28.9 months (95% CI, 24.3 months to not reached); the 24-month rate was 58.4%. Overall, 69.7% of patients reported treatment-related adverse events, most commonly pruritus (20.0%) and hypothyroidism (14.5%). Two deaths were treatment related (pneumonitis and cardiac arrest). CONCLUSION: First-line pembrolizumab monotherapy showed promising antitumor activity in nccRCC. The safety profile was similar to that observed in other tumor types.